Socio-Economic Aspects of Organizational Change Management - Premović, Jelena Đ. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
Radical changes faced by human society in the second half of the twentieth century had their repercussions on enterprises, imposing a new business philosophy of organizational behaviour and action as an imperative for success. The organizational changes represent constant challenges for HR managers, too. Acceptance and active participation in changes significantly affects the business success of the enterprises and society as a whole. In addition to a positive attitude towards change, employees feel and show a negative attitude in the form of resistance to the organizational change. The basic assumption that is made when implementing the process of change management and HR management in modern enterprises is that the human resources of the enterprises are the most important intangible business resources which have strategic importance for achieving competitive advantages. Based on this knowledge, the paper analyses the socio-economic aspects of the process of strategic change management and the attitude towards change in enterprises. The attitude towards change is analysed both from the perspective of the enterprises, HR managers, and from the perspective of employees. For that purpose, relevant theoretical material was used, as well as adequate scientifically based methodology in the form of methods of analysis and synthesis, induction and deduction, comparative and historical methods.
Keywords: organizational changes; change management; strategic management; human resources; attitude towards changes; resistance to changes